Analysis of the MILES cohort reveals determinants of disease progression and treatment response in lymphangioleiomyomatosis. Issue 4 (4th April 2019) - Gupta, Nishant; Lee, Hye-Seung; Young, Lisa R.; Strange, Charlie; Moss, Joel; Singer, Lianne G.; Nakata, Koh; Barker, Alan F.; Chapman, Jeffrey T.; Brantly, Mark L.; Stocks, James M.; Brown, Kevin K.; et al.
Introduction: The Multicenter International Lymphangioleiomyomatosis (LAM) Efficacy of Sirolimus (MILES) trial revealed that sirolimus stabilised lung function in patients with moderately severe LAM. The purpose of this study was to further examine the MILES cohort for the effects of racial, demographic, clinical and physiological patient characteristics on disease progression and treatment response in LAM. Methods: MILES subjects were stratified on the basis of menopausal status (pre-menopausal/post-menopausal), race (Asian/Caucasian), bronchodilator responsiveness (present/absent), initial forced expiratory volume in 1 s (FEV1 ; 51–70% versus ≤50% predicted) and tuberous sclerosis complex (TSC) association (yes/no). A linear mixed effects model was used to compare slope differences, and nonparametric tests were used to compare medians and proportions between treatment groups in each stratum. Results: In the MILES placebo group, pre-menopausal patients declined 5-fold faster than post-menopausal patients (mean±se FEV1 slope −17±3 versus −3±3 mL·month −1 ; p=0.003). Upon treatment with sirolimus, both the pre-menopausal (−17±3 versus −1±2 mL·month −1 ; p<0.0001) and post-menopausal patients (−3±3 versus 6±3 mL·month −1 ; p=0.04) exhibited a beneficial response in mean±se FEV1 slope compared with the placebo group. Race, LAM subtype, bronchodilator responsiveness or baseline FEV1 did not impact the rate of disease progression in the placebo group or treatment response in the sirolimus group. Menopausal status and race had differential effects on the adverse event profile of sirolimus. Baseline serum vascular endothelial growth factor (VEGF)-D >600 pg·mL −1 identified subgroups of patients who were more likely to decline on placebo and respond to treatment with sirolimus. Conclusions: In LAM patients, treatment with sirolimus is beneficial regardless of menopausal status, race, bronchodilator responsiveness, baseline FEV1 or TSC association. Serum VEGF-D and menopausal status can help inform therapeutic decisions. Menopausal status and serum vascular endothelial growth factor-D levels are clinically useful variables that should be taken into consideration when making therapeutic decisions and designing clinical trials for patients with lymphangioleiomyomatosis http://ow.ly/ijGB30nrNCB